(untitled) (Journal of Applied Learning and Teaching, 2023)
Academic dishonesty is an area of concern across all levels of education. While previous research has largely focused on what behaviours students engage in and what instructors do in response, little is known about why, and even less incorporates a theoretical framework. To contribute to the existing literature, our aim was to examine preservice secondary teachers’ beliefs about academic dishonesty. Moreover, we utilized Attribution Theory as our theoretical framework and examined how preservice teachers engage in causal search when presented with instances of academic dishonesty. Our results demonstrate that preservice teachers have strong beliefs about what is and what is not academic dishonesty; however, context matters. Indeed, when provided with descriptive scenarios compared to discrete behaviours, ratings of academic dishonesty were significantly higher in the former than the latter. Moreover, preservice teachers draw on multiple pieces of information when engaging in the causal search process, identifying not only facts but also embellishments not present in the scenario and highlighting their beliefs around academic dishonesty. Recommendations for educators and administrators for supporting students are provided, as well as limitations and directions for future research.